Systems Biology Approach to Drug Development: Application to Toxicity Assessment of Cardiac Drugs - Rodriguez, B; Burrage, K; Gavaghan, D; Grau, V; Kohl, P; Noble, D (2010)
Side effects account for most of the instances of failure of candidate drugs at late stages of development. These development failures contribute to the exorbitant cost of bringing new compounds to market: a single withdrawal can represent a loss of more than 1 billion. Many unwanted actions of drugs affect the heart, resulting in potentially proarrhythmic alteration of ion channel function. Because these can be fatal, potential electrophysiological